Knowledge about the administration and regulation of high alert medications among nurses in Palestine: a cross-sectional study - Sa'ed H. Zyoud; Samar M. Khaled; Baraa M. Kawasmi; Ahed M. Habeba; Ayat T. Hamadneh; Hanan H. Anabosi; Asma'a Bani Fadel; Waleed M. Sweileh; Rahmat Awang; Samah W. Al-Jabi (BMC, 2019)
Abstract Background Medication errors (MEs) are unintended failures in the drug treatment process that can occur during prescription, dispensing, storing, preparation or administration of medications. High alert medications (HAMs) are defined as those medications that bear the highest risk of causing significant patient harm when used incorrectly, either due to their serious adverse events or to a narrow therapeutic window. Nurses are responsible for administration of HAMs; incorrect administration can have a significant clinical outcome. This study aimed to assess the level of knowledge of HAMs among nurses in government hospitals in West Bank, Palestine. Methods A cross-sectional study was conducted in 2015, in West Bank, Palestine. Data were collected via a face to face interview questionnaire, which was taken from a previous study. Data were collected by convenient sampling. The questionnaire consisted of four parts: demographic characteristics of the nurses, drug administration knowledge (10 true-false questions), drug regulation knowledge (10 true-false questions), and self-evaluation. Results A total of 280 nurses participated in the study; these nurses were working in the emergency room (ER), intensive care unit (ICU), paediatric or medical ward. The response rate was 93%. Nurses were found to have insufficient knowledge about HAMs; 67.1% of participants had a score of less than 70%, with a mean total score of 59.9 ± 15.1. Factors associated with sufficient knowledge among nurses were HAMs training and ICU training, both with p-values of 0.002. Nurses with a master degree, those working in the ICU ward, head nurses, and male nurses were the most knowledgeable groups, with a p-values < 0.001. 81.8% of respondents hoped to obtain additional training. The leading obstacles reported were inconsistent opinions between doctors and nurses (37.9%), and no established standard operating procedure for HAMs (37.1%). Conclusions Lack of knowledge was one of the obstacles that nurses encountered during administration of HAMs which might result in MEs. Nurses reported that they would like to have additional training to update their pharmacology knowledge. Nurses could benefit from additional continuing education and training programs.